Launch event of the AgriTech4Egypt Innovation Challenge - Zaccari, Claudia; Al-saffar, Reem Hazim Khalis; Menza, Gianpiero (2024)
The AgriTech4Egypt Innovation Challenge is powered by CGIAR Accelerate for Impact Platform (A4IP) and co-organized with CGIAR Centers–The Alliance of Bioversity International and CIAT, ICARDA, IWMI, and IFPRI–and the Academy of Scientific Research and Technology (ASRT) of Egypt. This project is endorsed by the Ministry of Higher Education and Scientific Research of Egypt (MOHESR) and supported by PRIMA, Climate Resilient Africa Fund (CRAF), ALEX BANK, Syngenta Foundation for Sustainable Agriculture (SFSA), and CGIAR Initiatives and units operating in the MENA region.